Pseudoprogression in patients with glioblastoma: clinical relevance despite low incidence - Radbruch, Alexander; Fladt, Joachim C.; Vollmuth, Philipp; Wiestler, Benedikt; Nowosielski, Martha; Bäumer, Philipp; Schlemmer, Heinz-Peter; Wick, Antje; Heiland, Sabine; Wick, Wolfgang; Bendszus, Martin (Neuro-Oncology, 2015)
AbstractBackground. According to the Response Assessment in Neuro-Oncology criteria, new enhancement within the radiation field on contrast enhanced T1-weighte